Association between diabetic eye disease and other complications of diabetes: Implications for care. A systematic review. Issue 3 (29th October 2018) - Pearce, Ian; Simó, Rafael; Lövestam‐Adrian, Monica; Wong, David T.; Evans, Marc
Abstract : The aim of this systematic review was to examine the associations between diabetic retinopathy (DR) and the common micro‐ and macrovascular complications of diabetes mellitus, and how these could potentially affect clinical practice. A structured search of the PubMed database identified studies of patients with diabetes that assessed the presence or development of DR in conjunction with other vascular complications of diabetes. From 70 included studies, we found that DR is consistently associated with other complications of diabetes, with the severity of DR linked to a higher risk of the presence of, or of developing, other micro‐ and macrovascular complications. In particular, DR increases the likelihood of having or developing nephropathy and is also a strong predictor of stroke and cardiovascular disease, and progression of DR significantly increases this risk. Proliferative DR is a strong risk factor for peripheral arterial disease, which carries a risk of lower extremity ulceration and amputation. Additionally, our findings suggest that a patient with DR has an overall worse prognosis than a patient without DR. In conclusion, this analysis highlights the need for a coordinated and collaborative approach to patient management. Given the widespread use of DR screening programmes that can be performed outside of an ophthalmology office, and the overall cost‐effectiveness of DR screening, the presence and severity of DR can be a means of identifying patients at increased risk for micro‐ and macrovascular complications, enabling earlier detection, referral and intervention with the aim of reducing morbidity and mortality among patients with diabetes. Healthcare professionals involved in the management of diabetes should encourage regular DR screening.